Bioinformatics of Cancer ncRNA in High Throughput Sequencing: Present State and Challenges - Jorge, Natasha A.; Ferreira, Carlos G.; Passetti, Fabio (Frontiers in Genetics, 2012)
The numerous genome sequencing projects produced unprecedented amount of data providing significant information to the discovery of novel noncoding RNA (ncRNA). Several ncRNAs have been described to control gene expression and display important role during cell differentiation and homeostasis. In the last decade, high throughput methods in conjunction with approaches in bioinformatics have been used to identify, classify and evaluate the expression of hundreds of ncRNA in normal and pathological states, such as cancer. Patient outcomes have been already associated with differential expression of ncRNAs in normal and tumoral tissues, providing new insights in the development of innovative therapeutic strategies in oncology. In this review, we present and discuss bioinformatics advances in the development of computational approaches to analyze and discover ncRNA data in oncology using high throughput sequencing technologies.